Digestible protein requirements and muscle growth in juvenile tambaqui (Colossoma macropomum) - Buzollo, Hellen [UNESP]; Sandre, Lidiane Cristina Gonçalves de [UNESP]; Neira, Ligia Maria [UNESP]; Nascimento, Thiago Matias Torres do [UNESP]; Jomori, Rosângela Kiyoko; Carneiro, Dalton José [UNESP] (Hindawi, 2019)
Several investigations have been carried out to improve the productivity of tambaqui, an economically important fish species in Brazil and other Latin American countries. This study determined the digestible protein (DP) requirements in juvenile tambaqui by assessing their productive performance and nutritional efficiency. It also evaluated the effects of different dietary DP levels on the morphology and cellularity of skeletal fast muscle fibres. The 1750 tambaqui tested (6.53 ± 0.43 g body weight, 7.58 ± 0.18 cm length) were randomly distributed into 35 tanks. Fish were fed one of the seven isocaloric diets, which contained 140, 170, 200, 230, 260, 290 or 320 g/kg DP. The DP requirement, calculated by segmented (broken line) regression of weight gain data, was 290 g/kg. An increase in diet DP to 290 g/kg significantly improved final weight, weight gain, feed intake, specific growth rate and crude protein gain, and changed fibre diameter in deep muscle. Muscle fibres were randomly distributed into a mosaic pattern, characterized by fibres with different diameters. Treatments with 290 and 320 g/kg DP increased the frequency of large-diameter fibres (>50 µm), indicating hypertrophic growth of skeletal muscle during the juvenile phase, which occurred in conjunction with hyperplasia.
Keywords: digestible protein requirement; fish; hyperplasia; hypertrophy; muscle; productive performance; tambaqui